Effectiveness of Providing Murotal Therapy of Surah Ar-Rahman on Pain of NY R with Post-Op Thyroidectomy in the Late Room of Prof. Dr. Margono Soekarjo Hospital - Nur Aeni, Rina; Susanti, Indri Heri (Universitas Ibn Khaldun Bogor, 2024)
Nursing care is an integral part of health services for patients diagnosed with thyroid tumors. This study aims to explore the nursing care provided to Ms. R, a patient diagnosed with thyroid tumors in the Teratai Room, Prof. Dr. Margono Soekarjo Hospital. The method used is the nursing process including assessment, nursing diagnosis, planning, implementation, and evaluation. The results of the assessment showed that there were main complaints in the form of swelling in the neck area, swallowing disorders, and anxiety. The nursing diagnoses found included ineffective airway, nutritional imbalance, and anxiety. The interventions provided included airway management, adequate nutrition, and psychological therapy to reduce anxiety. The evaluation showed an improvement in the patient's clinical condition after the intervention was carried out continuously. This study concludes that comprehensive and focused nursing care can improve the quality of life of patients with thyroid tumors.